Analysis of the Implementation of the Contract in TikTok Affiliate Marketing Strategy - Khoyril Waro; Abdur Rohman (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the types of Islamic contracts (akad) that are relevant to affiliate marketing practices on the TikTok platform and to examine their compliance with the principles of Islamic commercial jurisprudence (muamalah). Affiliate marketing represents a digital marketing strategy that involves collaboration between content creators (affiliators), product owners, and consumers through social media platforms. From the perspective of Islamic law, this practice can be examined through three primary types of contracts: samsarah (intermediation), ju‘ālah (reward-based contract), and wakālah bil ujrah (agency with compensation). Each of these contracts possesses a legitimate legal basis and aligns with sharia principles. This research adopts a qualitative method with a literature review approach, by analyzing various academic sources such as scholarly journals, books, and authoritative documents relevant to the topic. The findings indicate that the TikTok affiliate system can be implemented in accordance with sharia, provided it fulfills the essential elements and conditions of valid contracts and remains free from prohibited elements such as gharar (uncertainty), riba (usury), and dharar (harm). These results affirm that the integration of Islamic economic values within digital marketing practices enables the formation of fair, transparent, and ethically sound transactions. Furthermore, it demonstrates the relevance and adaptability of Islamic commercial law in addressing the challenges of the modern digital economy.